Unusual Cervical Spinal Cord Toxicity Associated with Intra-arterial Carboplatin, Intra-arterial or Intravenous Etoposide Phosphate, and Intravenous Cyclophosphamide in Conjunction with Osmotic Blood Brain–Barrier Disruption in the Vertebral Artery - Fortin, David; McAllister, Leslie D.; Nesbit, Gary; Doolittle, Nancy D.; Miner, Michael; Hanson, E. Jerome; Neuwelt, Edward A. (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: When the clinical and radiologic characteristics of an unusual cervical spinal cord complication of intra-arterial (IA) chemotherapy with blood brain–barrier (BBB) disruption in the vertebral circulation are documented. Seven cases are reported and analyzed in search of a pathophysiologic explanation.METHODS: We retrospectively identified 94 patients who received a total of 380 standardized regimens of IA carboplatin, IA or IV etoposide phosphate, and IV cyclophosphamide infusion in conjunction with osmotic BBB disruption of the vertebral artery. We describe seven of those patients in whom unexpected neck pain developed followed by neurologic symptoms primarily in the upper extremities.RESULTS: The symptoms correlated with MR abnormalities (T1 hypointensity, T2 hyperintensity, and unusual contrast enhancement) in the cervical spinal cord, usually involving the gray matter. The neurologic deficits and MR changes were generally transient. One patient who received a flu vaccination 48 hours before the chemotherapy incurred progressive myelitis and expired.CONCLUSION: The pathophysiology of this complication is probably multifactorial but may be related to vascular streaming and an atypical inflammatory toxic reaction to carboplatin and etoposide. The complication has not recurred during a 6-month period following modification of the protocol.